Evaluation of Maturity and its Correlated Traits in an Unadapted F2 Maize Population (Journal of Science and Technology, 2016)
This study was conducted to understand the mode of inheritance of maturity in an adapted by unadapted F2 maize population and to identify the best progeny of introgressed population to be used for single cross hybrid development. Thermal indices (growing degree days or heat units or thermal time), calculated from minimum and maximum temperatures, and a base temperature were used to measure the maturity of maize progenies. Two hundred and eleven (211) S1 families developed from a cross between an adapted Corn Belt maize inbred line (B73) and an unadapted maize population and their testcrosses were evaluated in two planting dates and two locations in 1995. Maturity was quantitatively inherited as trangressive segregation for all the traits observed, and few factors were responsible for the expression of maturity in maize. Earliness was dominant to lateness. Maturity measured in thermal units was better than calendar days. Based on the performance of the test crosses up to ten S1 lines could be selected for the development of single cross hybrids that could produce more grain than the check hybrids